Innovative Educational Initiatives to Train Psychodynamic Psychiatrists in Underserved Areas of the World - Alfonso, César A; Michael, Marco Christian; Elvira, Sylvia Detri; Zakaria, Hazli; Kalayasiri, Rasmon; Adlan, Aida Syarinaz A; Moinalghorabaei, Mahdieh; Lukman, Petrin Redayani; San'ati, Mohammad; Duchonova, Katerina; Sullivan, Timothy B (The Psychiatric clinics of North America, 2018)
Psychodynamic psychiatry remains a challenging subject to teach in underserved areas, where enthusiasm to learn is substantial. Besides logistical and psychiatric workforce shortcomings, sensible cultural adaptations to make psychodynamic psychiatry relevant outside of high-income countries require creative effort. Innovative pedagogical methods that include carefully crafted mentoring and incorporate videoconferencing in combination with site visits can be implemented through international collaborations. Emphasis on mentoring is essential to adequately train future psychodynamic psychotherapy supervisors. Examples of World Psychiatric Association initiatives in countries such as Indonesia, Iran, Malaysia, and Thailand are presented as possible models to emulate elsewhere.
Keywords: rozvojové země; Competency-Based Education; klinické kompetence; Psychotherapy; mezinárodní spolupráce; vzdělávání podle kvalifikace; Transcultural psychiatry; International Cooperation; psychiatrie; Psychiatry; Clinical Competence; Low-income and middle-income countries; kurzy a stáže v nemocnici; Humans; Psychiatric education; celosvětové zdraví; psychodynamická psychoterapie; Global Health; Psychotherapy, Psychodynamic; Internship and Residency; Developing Countries; Psychodynamic psychiatry; lidé